Increased bacterial load of Filifactor alocis in deep periodontal pockets discriminate between periodontitis stage 3 and 4 - Faisal, Reem H.; Ali, Alaa O. (Frontiers in Oral Health, 2025)
IntroductionIncreasing evidence supports the association of Filifactor alocis with periodontitis; therefore, this work was conducted to assess the prevalence and proportion of F. alocis in subgingival biofilm samples from patients with periodontitis stage 3 and 4, and its potential to differentiate between these stages.MethodsThis cross-sectional study included 50 periodontitis patients from whom subgingival biofilm samples were collected using paper points. This was followed by recording clinical periodontal parameters including the plaque index, bleeding on probing, probing pocket depth (PPD), and clinical attachment loss (CAL). The total loads of bacteria and F. alocis were determined via quantitative PCR.ResultsAll patients were diagnosed with periodontitis stage 3/4 and grade B/C, with a total of 727 periodontal pockets, which were pooled (n = 114) for microbiological analysis. Qualitative and quantitative analyses indicated that the total bacterial load and prevalence of F. alocis were highest in stage 4 and grade C cases, which were also increased with increasing PPD and severity of CAL. An ROC analysis indicated that both the total bacterial load and F. alocis concentration could significantly discriminate stage 3 and 4 periodontitis. The regression model suggested that a one-unit increase in PPD, and CAL could explain a 23.9% and 14.9% increase in the F. alocis concentration, respectively.ConclusionThe results demonstrate that the prevalence of F. alocis is increased in severe periodontitis cases, mainly at sites with deep periodontal pockets and greater attachment loss. Additionally, this bacterium possesses the diagnostic potential to differentiate periodontitis cases of different severities.